Conceptions of ability and self-determined motivation in young Spanish athletes - Moreno-Murcia,Juan Antonio (2014)
This investigation examined the relationship between implicit ability beliefs and self-determined motivation. The sample was comprised of 775 young athletes between the ages of 12 and 17 competing at national level in Spain. The participants completed the Spanish version of the Conceptions of the Nature of Athletic Ability Questionnaire (CNAAQ-2) and the Sport Motivation Scale (SMS). The results revealed a positive and significant correlation between stable ability beliefs and learning ability, and between self-determined motivation and perceived sports ability. To the contrary, stable entity beliefs were negatively correlated with self-determined motivation. Competitiveness in sports was significantly predicted by self-determined motivation, and the latter, in its turn, was positively predicted by learning belief and negatively by stable entity beliefs.